Inorganic Molecular Chain Nb2Se9: Synthesis of Bulk Crystal and One-Atom-Thick Level Exfoliation - Oh, Seungbae; Chae, Sudong; Kim, Bum Jun; Siddiqa, Akhtar J.; Choi, Kyung Hwan; Jang, Woo Sung; Lee, Keun Ho; Kim, Hyo Yeol; Lee, Dong Kyu; Kim, Young Min; Yu, Hak Ki; Choi, Jae Young (Physica Status Solidi - Rapid Research Letters, 2018)
A novel one-dimensional (1D) inorganic material, Nb2Se9, which can be separated into atomic-level, is synthesized through chemical reaction between Nb and Se sources. Nb2Se9 and Se crystals are formed under an excess Se condition to avoid other phase such as NbSe3, and the residual Se can be removed by heat treatment; thus, high-purity Nb2Se9 crystals can be obtained. The one-atom-thick level Nb2Se9 nanochains are successfully obtained by mechanical exfoliation and dispersion in a solvent. The covalently bonded Nb2Se9 chain, when isolated from its three-dimensional bulk material, is expected to have unique physical properties based on electron confinement in the 1D chain structure and the absence of dangling bonds. In addition, it has excellent thermal stability (up to 500 °C) and can be widely used in various fields.
Keywords: Covalently bonded; Electron confinement; exfoliation; Inorganic materials; Mechanical exfoliation; Molecular chains; Nb2Se9; Van der waals; 1D inorganic molecular chain; exfoliation; Nb2Se9; van der Waals bonding